Ribociclib-Loaded Ethylcellulose-Based Nanosponges: Formulation, Physicochemical Characterization, and Cytotoxic Potential against Breast Cancer - Mohammed Muqtader Ahmed; Farhat Fatima; Amer Alali; Mohd Abul Kalam; Khalid Alhazzani; Saurabh Bhatia; Sultan Alshehri; Mohammed M. Ghoneim (Adsorption Science & Technology, 2022)
In the present study, ribociclib-loaded nanosponges (RCNs) composed of ethylcellulose and polyvinyl alcohol were developed using an emulsion-solvent evaporation method. Preliminary evaluations of the developed RCNs (RCN1 to RCN7) were performed in terms of size, polydispersity index (PDI), zeta potential (ZP), entrapment efficiency (EE), and drug loading (DL), which allowed us to select the optimized formulation. RCN3 was selected as the optimized carrier system with particle size (363.5±4.8 nm), PDI (0.292±0.012), zeta potential (−18.5±0.05 mV), EE (81.35±1.64%), and DL (21.96±0.28%). Further, the optimized nanosponges (RCN3) were subjected to FTIR, XRD, DSC, and SEM studies, and results confirmed the proper encapsulation of the drug within the porous polymeric matrix. In vitro drug release studies showed that the drug release was significantly enhanced with a maximum drug release through RCN3 formulation (81.85±0.37%) and followed the Higuchi model. Moreover, the RCN3 system showed greater cytotoxicity than free ribociclib (RC) against MDA-MB-231 and MCF-7 breast cancer cell lines. The percentage of apoptosis induced by RCN3 was found significantly higher than that of free RC (p<0.05). Overall, ribociclib-loaded ethylcellulose nanosponges could be a potential nanocarrier to enhance the effectiveness of ribociclib in breast cancer treatment.